Alloy catalyst, preparation method thereof and application of alloy catalyst in low-temperature catalytic cracking of methane
By preparing Ni-Co-In alloy catalyst, the problem of insufficient activity and stability of methane catalytic cracking catalyst in the prior art is solved, and efficient catalytic methane cracking at lower temperatures is achieved, with good stability and high stability methane conversion rate and controllable degree of graphitization of carbon products.
Patent Information
- Application Number
- CN202411367102.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The existing methane catalytic cracking technology catalysts are insufficient in activity and stability at high temperatures, making it difficult to achieve efficient catalytic reactions at lower temperatures.
Using Ni-Co-In alloy catalyst, the hydrothermal reaction was carried out by dropwise addition of oxalic acid solution to a mixed solution of nickel nitrate, cobalt nitrate and indium nitrate, and then heat treatment was performed under the atmosphere of CH4-Ar mixed stream to prepare a high catalytic activity. and stable Ni-Co-In alloy catalyst for low temperature catalytic cracking of methane.
At the reaction temperature of 700 to 990°C, the Ni-Co-In alloy catalyst exhibits high methane conversion and stability, especially at 800°C, the methane conversion rate can reach 52%, and at 91% at 990°C, and remains In solid state, and the degree of graphitization of the carbon product is controllable.
Smart Images

Figure CN119236949A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an alloy catalyst and a preparation method thereof and application in low-temperature catalytic cracking of methane, belonging to the technical field of methane cracking hydrogen production catalyst and preparation method thereof. Background Art
[0002] Catalytic methane cracking to produce hydrogen is a green, environmentally friendly, efficient and clean hydrogen production technology. Methane is decomposed at high temperature to produce hydrogen and solid carbon, without producing carbon oxides. The gas only contains hydrogen and unreacted methane. Further liquefaction separation or membrane separation technology can produce hydrogen with a purity of 99%. Compared with the further complex separation process (processing carbon dioxide or carbon monoxide), this process is simple, less energy-consuming and environmentally friendly.
[0003] Methane cracking is an endothermic reaction. The energy consumed to generate hydrogen is 37.8 kJ / mol. The CH bond in the methane molecule is very stable, and it requires a higher temperature (over 1200°C) to completely decompose. Using a suitable and reliable catalyst can reduce the activation energy of the CH bond and reduce the requirement for reaction temperature. Therefore, it is crucial to select and design a suitable catalyst.
[0004] At present, the research focus of methane cracking to produce hydrogen is mainly on the preparation of efficient, easy-to-obtain, low-cost and stable catalysts. Among the catalysts that catalyze the methane cracking reaction to produce hydrogen, 3d transition metal elements (Co, Ni, Fe) have great catalytic activity for the decomposition of hydrocarbons. However, metal Ni will quickly aggregate and sinter or be coated with carbon above 600°C and become inactivated, thus affecting its stability and life. Metal Fe helps to generate products with specific morphology and still has good activity and stability in the range of 700-1000°C, but its catalytic activity is lower than that of metal Ni. Studies have shown that compared with single metal catalysts, the electron density and geometric properties of the catalyst surface of bi / multi-metal catalysts are changed, thereby affecting their catalytic reaction path, resulting in different catalytic mechanisms, and ultimately improving the catalytic activity of the catalyst. However, the existing bi / multi-metal catalysts generally exhibit high catalytic activity at a temperature above 1000°C for the catalytic methane cracking reaction. Therefore, it is very necessary to provide a catalyst with high catalytic activity at a lower temperature. Summary of the invention
[0005] Aiming at the problems of low efficiency and high catalytic reaction temperature of existing methane catalytic cracking, the present invention provides an alloy catalyst and a preparation method thereof and application in low-temperature catalytic cracking of methane.
[0006] The technical solution of the present invention:
[0007] One of the purposes of the present invention is to provide a method for preparing an alloy catalyst, the method comprising the following steps:
[0008] (1) adding an oxalic acid solution dropwise to a mixed solution containing nickel nitrate, cobalt nitrate and indium nitrate, and transferring the solution to an autoclave for hydrothermal reaction after the addition is completed. After the reaction is completed, washing and drying the precipitate to obtain a Ni-Co-In alloy precursor;
[0009] (2) The Ni-Co-In alloy precursor is heat treated in a CH4-Ar mixed flow atmosphere to obtain a Ni-Co-In alloy catalyst.
[0010] It is further defined that the molar ratio of nickel nitrate, cobalt nitrate and indium nitrate in (1) is 2:1:1 to 5:0:1.
[0011] It is further defined that in (1), oxalic acid is added in a stoichiometric amount to completely react with the nickel nitrate, cobalt nitrate and indium nitrate in the mixed solution.
[0012] It is further defined that the hydrothermal reaction temperature in (1) is 100-200°C and the reaction time is 10-20h.
[0013] It is further defined that the drying treatment conditions in (1) are: vacuum drying at 40-80°C for 24-48 hours.
[0014] It is further defined that the flow rate of the CH4-Ar mixed flow in (2) is 20-80 mL / min, and the volume ratio of CH4 to Ar is 1:1.
[0015] It is further defined that the heat treatment temperature in (2) is 200-600°C and the time is 30-90 minutes.
[0016] A second object of the present invention is to provide an alloy catalyst obtained by the above preparation method.
[0017] It is further defined that the alloy catalyst is used to catalyze methane cracking reaction.
[0018] The third object of the present invention is to provide a method for low-temperature catalytic cracking of methane, which uses the above-mentioned alloy catalyst as a cracking reaction catalyst, and the cracking reaction conditions are: under standard atmospheric pressure, the reaction temperature is 700-990°C, the CH4 gas flow rate is 6-60mL / min, and the protective gas Ar flow rate is 10-100mL / min.
[0019] Beneficial effects:
[0020] (1) The Ni-Co-In alloy catalyst provided by the present invention utilizes alloying between nickel, cobalt and indium to change the electron distribution around the metal, thereby increasing the catalytic activity of the catalyst. In addition, the alloy catalyst contains a small number of elements and the ratio between the elements is easy to control. The ratio of nickel, cobalt and indium elements in the alloy can be controlled by controlling the molar ratio of nickel ions, cobalt ions and indium ions in the precursor, thereby achieving the regulation of its catalytic active sites and methane cracking catalytic performance. Specifically, the present invention obtains a catalyst with high catalytic activity and stability by regulating the ratio of nickel, cobalt and indium elements (Ni 0.65 Co 0.10 In 0.25 ), the methane conversion rate can reach 52% at a reaction temperature of 800°C and maintain good stability within 120 minutes of reaction.
[0021] (2) The synthesis method of the Ni-Co-In alloy catalyst provided by the present invention is simple and easy to produce in large quantities, and the operation process is safe and easy to realize industrialization.
[0022] (3) The Ni-Co-In alloy catalyst prepared by the present invention can not only meet the requirements of methane cracking under low temperature conditions, but also has a relatively high conversion rate and stability, and always remains in a solid state at a reaction temperature of 700 to 990°C. 0.65 Co 0.10 In 0.25 The methane conversion rate of the catalyst reached 91%. In addition, the graphitization degree of the carbon product obtained by the reaction was controllable, especially Ni 0.65 Co 0.10 In 0.25 The alloy catalyst has the highest graphitization degree of the carbon product after the methane catalytic cracking reaction at a reaction temperature of 900° C. This shows that the alloy catalyst prepared by the method provided by the present invention can be regulated differently according to different application scenarios and has a wide range of application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 X-ray powder diffraction patterns of Ni-Co-In alloy catalysts prepared in different embodiments;
[0024] Figure 2 X-ray powder diffraction patterns of Ni-Co-In alloy catalysts prepared in different embodiments after catalyzing methane cracking reaction at 800°C for 30 minutes;
[0025] Figure 3 The Ni prepared in Example 4 0.65 Co 0.10 In 0.25 Microscopic morphology of alloy catalyst (different magnifications);
[0026] Figure 4 The Ni prepared in Example 4 0.65 Co 0.10 In 0.25 Microscopic morphology of the alloy catalyst after catalytic methane cracking reaction at 800℃ for 30 minutes (different magnifications);
[0027] Figure 5 The Ni prepared in Example 4 0.65 Co 0.10 In 0.25 Raman spectra of the product carbon after catalytic cracking reaction of the alloy catalyst at different temperatures for 30 minutes;
[0028] Figure 6 The conversion rate of methane cracking catalyzed by the Ni-Co-In alloy catalyst prepared in different embodiments at a reaction temperature of 800°C;
[0029] Figure 7 The Ni prepared in Example 4 0.65 Co 0.10 In 0.25 Methane conversion rate of alloy catalysts catalyzing methane cracking reaction at different reaction temperatures for 10 min;
[0030] Figure 8 The graph is a stability test result of Ni-Co-In alloy catalysts prepared in different embodiments at a reaction temperature of 800°C. DETAILED DESCRIPTION
[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0032] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0033] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0034] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art, and the purity of the solid and liquid reagents used is analytically pure.
[0035] Example 1
[0036] In this example, Ni 0.50 Co 0.25 In 0.25 The process of alloy catalyst is as follows:
[0037] (1) 1.309 g Ni(NO3)2·6H2O, 0.655 g Co(NO3)2·6H2O and 0.677 g InN3O9·xH2O were dissolved in 30 mL deionized water, which was recorded as solution A. 1.276 g C2H2O4·2H2O was dissolved in 30 mL deionized water, which was recorded as solution B. Solution B was slowly titrated into solution A using a constant pressure burette (titration rate was 1.5-3 mL / min), and magnetic stirring was performed for 60 min during and after the titration. The suspension was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and maintained at 120°C for 12 h. After cooling to room temperature, a light blue precipitate was obtained. The obtained precipitate was centrifuged and washed three times with deionized water and ethanol respectively.
[0038] (2) The light blue precipitate obtained by centrifugation is placed in a vacuum drying oven at 60° C. and vacuum dried for 20 to 24 hours. The obtained light blue powder is the Ni-Co-In alloy precursor.
[0039] (3) Alloy particles were synthesized by heating the prepared Ni-Co-In alloy precursor powder in a CH4-Ar mixed flow (CH4 / Ar=1) with a total flow rate of 40 mL / min. The precursor was heated to 450°C and maintained for 30 min to dehydrate the Ni-Co-In alloy precursor and decompose it into Ni-Co-In alloy. The product was named Ni 0.50 Co 0.25 In 0.25 .
[0040] Example 2
[0041] In this example, Ni 0.55 Co 0.20 In 0.25 The process of alloy catalyst is as follows:
[0042] (1) 1.439 g Ni(NO3)2·6H2O, 0.524 g Co(NO3)2·6H2O and 0.677 g InN3O9·xH2O were dissolved in 30 mL deionized water, which was recorded as solution A. 1.276 g C2H2O4·2H2O was dissolved in 30 mL deionized water, which was recorded as solution B. Solution B was slowly titrated into solution A using a constant pressure burette (titration rate was 1.5-3 mL / min), and magnetic stirring was performed for 60 min during and after the titration. The suspension was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and maintained at 120°C for 12 h. After cooling to room temperature, a light blue precipitate was obtained. The obtained precipitate was centrifuged and washed three times with deionized water and ethanol respectively.
[0043] (2) The light blue precipitate obtained by centrifugation is placed in a vacuum drying oven at 60°C and vacuum dried for 24 hours. The obtained light blue powder is the Ni-Co-In alloy precursor.
[0044] (3) Alloy particles were synthesized by heating the prepared Ni-Co-In alloy precursor powder in a CH4-Ar mixed flow (CH4 / Ar=1) with a total flow rate of 40 mL / min. The precursor was heated to 450°C and maintained for 30 min to dehydrate the Ni-Co-In alloy precursor and decompose it into Ni-Co-In alloy. The product was named Ni 0.55 Co 0.20 In 0.25 .
[0045] Example 3
[0046] In this example, Ni 0.60 Co 0.15 In 0.25 The process of alloy catalyst is as follows:
[0047] (1) 1.570 g Ni(NO3)2·6H2O, 0.393 g Co(NO3)2·6H2O and 0.677 g InN3O9·xH2O were dissolved in 30 mL deionized water, which was recorded as solution A. 1.276 g C2H2O4·2H2O was dissolved in 30 mL deionized water, which was recorded as solution B. Solution B was slowly titrated into solution A using a constant pressure burette (titration rate was 1.5-3 mL / min), and magnetic stirring was performed for 60 min during and after the titration. The suspension was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and maintained at 120°C for 12 h. After cooling to room temperature, a light blue precipitate was obtained. The obtained precipitate was centrifuged and washed three times with deionized water and ethanol respectively.
[0048] (2) The light blue precipitate obtained by centrifugation is placed in a vacuum drying oven at 60°C and vacuum dried for 24 hours. The obtained light blue powder is the Ni-Co-In alloy precursor.
[0049] (3) Alloy particles were synthesized by heating the prepared Ni-Co-In alloy precursor powder in a CH4-Ar mixed flow (CH4 / Ar=1) with a total flow rate of 40 mL / min. The precursor was heated to 450°C and maintained for 30 min to dehydrate the Ni-Co-In alloy precursor and decompose it into Ni-Co-In alloy. The product was named Ni 0.60 Co 0.15 In 0.25 .
[0050] Example 4
[0051] In this example, Ni 0.65 Co 0.10 In 0.25 The process of alloy catalyst is as follows:
[0052] (1) 1.701 g Ni(NO3)2·6H2O, 0.262 g Co(NO3)2·6H2O and 0.677 g InN3O9·xH2O were dissolved in 30 mL deionized water, which was recorded as solution A. 1.276 g C2H2O4·2H2O was dissolved in 30 mL deionized water, which was recorded as solution B. Solution B was slowly titrated into solution A using a constant pressure burette (titration rate was 1.5-3 mL / min), and magnetic stirring was performed for 60 min during and after the titration. The suspension was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and maintained at 120°C for 12 h. After cooling to room temperature, a light blue precipitate was obtained. The obtained precipitate was centrifuged and washed three times with deionized water and ethanol respectively.
[0053] (2) The light blue precipitate obtained by centrifugation is placed in a vacuum drying oven at 60°C and vacuum dried for 24 hours. The obtained light blue powder is the Ni-Co-In alloy precursor.
[0054] (3) Alloy particles were synthesized by heating the prepared Ni-Co-In alloy precursor powder in a CH4-Ar mixed flow (CH4 / Ar=1) with a total flow rate of 40 mL / min. The precursor was heated to 450°C and maintained for 30 min to dehydrate the Ni-Co-In alloy precursor and decompose it into Ni-Co-In alloy. The product was named Ni 0.65 Co 0.10 In 0.25 .
[0055] Example 5
[0056] In this example, Ni0.70 Co 0.05 In 0.25 The process of alloy catalyst is as follows:
[0057] (1) 1.832 g Ni(NO3)2·6H2O, 0.131 g Co(NO3)2·6H2O and 0.677 g InN3O9·xH2O were dissolved in 30 mL deionized water, which was recorded as solution A. 1.276 g C2H2O4·2H2O was dissolved in 30 mL deionized water, which was recorded as solution B. Solution B was slowly titrated into solution A using a constant pressure burette (titration rate was 1.5-3 mL / min), and magnetic stirring was performed for 60 min during and after the titration. The suspension was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and maintained at 120°C for 12 h. After cooling to room temperature, a light blue precipitate was obtained. The obtained precipitate was centrifuged and washed three times with deionized water and ethanol respectively.
[0058] (2) The light blue precipitate obtained by centrifugation is placed in a vacuum drying oven at 60°C and vacuum dried for 24 hours. The obtained light blue powder is the Ni-Co-In alloy precursor.
[0059] (3) Alloy particles were synthesized by heating the prepared Ni-Co-In alloy precursor powder in a CH4-Ar mixed flow (CH4 / Ar=1) with a total flow rate of 40 mL / min. The precursor was heated to 450°C and maintained for 30 min to dehydrate the Ni-Co-In alloy precursor and decompose it into Ni-Co-In alloy. The product was named Ni 0.70 Co 0.05 In 0.25 .
[0060] Effect example
[0061] (1) The Ni-Co-In ternary alloy powders of different proportions prepared in Examples 1 to 5 were tested by X-ray powder diffraction. The test results are as follows: Figure 1 As shown, through Figure 1 It can be seen that the XRD patterns of all alloy samples only show a series of peaks corresponding to the face-centered cubic (fcc) phase, which indicates that a Ni-Co-In solid solution is formed, which is different from the individual diffraction peaks presented by the physically mixed metal samples. The grain size of the Ni-Co-In alloy particles is further calculated, ranging from 15.6 to 18.8 nm.
[0062] (2) Ni-Co-In ternary alloy powders in different proportions prepared in Examples 1 to 5 were used as catalysts to catalyze methane cracking reactions.
[0063] Specifically, a fixed mass of Ni-Co-In alloy catalyst is placed in the center of a quartz tube reactor. To ensure that an equal mass of sample is used for each test, it can be assumed that the contact time of methane on the catalyst particles is approximately the same in each test. A K-type thermocouple covered with a quartz thermocouple sleeve is placed near the catalyst bed to detect the temperature of the catalyst bed. The reactor is installed vertically in an electric furnace, and methane cracking experiments are carried out at standard atmospheric pressure. The feed gas is CH4, and the gas flow rate is 6mL / min. The intelligent electric furnace heats the center of the reaction tube to a reaction temperature of 800°C (under a protective atmosphere with an Ar flow rate of 100mL / min). When the reactor temperature reaches the set temperature, the feed gas is introduced to start the catalytic methane cracking reaction. After 30 minutes of reaction, the catalyst is tested by X-ray powder diffraction. The test results are as follows. Figure 2 As shown, the diffraction peaks of graphite carbon and Ni-Co-In alloy can be observed from the figure, which indicates that after the methane cracking reaction, the catalyst still exists in an alloy state.
[0064] (3) The Ni prepared in Example 4 0.65 Co 0.10 In 0.25 The microscopic morphology of the alloy catalyst and the catalyst after the methane cracking reaction as described in (2) was characterized, and the SEM morphology photos are shown in Figure 3 and Figure 4 As shown by Figure 3 It can be seen that most of the Ni-Co-In particles are blocky, with rough surfaces and different particle sizes. There are a large number of pore structures on the catalyst surface, which helps to provide more reaction sites and increase the activity of the catalyst. Figure 4 It can be seen that Ni 0.65 Co 0.10 In 0.25 After the methane cracking reaction, the alloy catalyst generates a large amount of tubular carbon nanofiber materials, which are carbon nanotubes or carbon nanofibers, with diameters and lengths of nanometers and micrometers respectively. The white particles in the figure are Ni-Co-In alloy particles after the catalytic reaction. It can be seen that they are located at the tip of the tubular carbon nanomaterial, indicating that the growth of the product carbon tube follows the tip growth mechanism. It can be analyzed that not all Ni-Co-In alloy particles are wrapped by carbon materials, which is one of the reasons why the catalyst has high stability.
[0065] (4) The Ni prepared in Example 4 0.65 Co 0.10 In 0.25 The alloy catalysts were used for methane cracking reaction at different temperatures, and then the product carbon was characterized by Raman spectroscopy. 0.65 Co 0.10 In 0.25The Raman spectra of the deposited carbon generated by the catalytic cracking of methane at 700℃, 800℃, 900℃ and 990℃ for 30 minutes are as follows: Figure 5 As shown, the I of deposited carbon D / I G The values are 1.26, 0.77, 0.40 and 1.46 respectively. The I D / I G The value is relatively small (0.40), indicating a high degree of graphitization.
[0066] Further, the Ni prepared in Example 4 0.65 Co 0.10 In 0.25 The methane conversion rate of the alloy catalyst during the methane cracking reaction at different temperatures was characterized. Specifically, the methane catalytic cracking reaction was carried out at a reaction temperature of 700-990°C for 10 minutes. Figure 7 As shown, because the methane cracking reaction is an endothermic reaction, increasing the reaction temperature greatly increases the methane conversion rate. When the reaction temperature is increased from 700°C to 990°C, the methane conversion rate increases from 40% to 91%.
[0067] (5) The catalytic activity of methane cracking reaction was tested on five Ni-Co-In alloy catalysts with different ratios prepared in Examples 1 to 5 in a fixed bed reactor (the timing started when the reactor temperature reached 800°C, and the reaction time was 30 minutes). Figure 6 It can be seen that the methane conversion rate of the prepared Ni-Co-In alloys with different ratios increases with the increase of nickel mole fraction (or the decrease of cobalt mole fraction). However, when the nickel content is too high, the number of metal nickel particles on the catalyst surface increases, which makes the relative spacing between these particles smaller, and it is easy to sinter or generate larger particles, thereby affecting the activity of the catalyst. 0.65 Co 0.10 In 0.25 The catalytic activity and stability of the sample are better than those of other samples.
[0068] (6) The catalytic stability of the five Ni-Co-In alloy catalysts with different ratios prepared in Examples 1 to 5 at 800° C. was characterized. Figure 8 As shown in Figure 2, all catalyst samples showed high initial catalytic activity. This is because nickel cobalt indium oxalate was converted into Ni-Co-In alloy by decomposition reaction before the reaction started. Within 120 min of methane catalytic cracking reaction, the methane conversion rate of the catalyst samples showed almost no downward trend. 0.50 Co 0.25 In 0.25After the alloy sample reacted for 90 minutes, the conversion rate decreased slightly. Therefore, it can be seen that the Ni-Co-In alloy catalyst prepared by the present invention has good stability.
[0069] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing an alloy catalyst, characterized in that: include: (1) adding an oxalic acid solution dropwise to a mixed solution containing nickel nitrate, cobalt nitrate and indium nitrate, and transferring the solution to an autoclave for hydrothermal reaction after the addition is completed. After the reaction is completed, washing and drying the precipitate to obtain a Ni-Co-In alloy precursor; (2) The Ni-Co-In alloy precursor is heat treated in a CH4-Ar mixed flow atmosphere to obtain a Ni-Co-In alloy catalyst.
2. The preparation method according to claim 1, characterized in that: The molar ratio of nickel nitrate, cobalt nitrate and indium nitrate in (1) is 2:1:1 to 5:0:
1.
3. The preparation method according to claim 1, characterized in that: (1) The hydrothermal reaction temperature is 100-200°C and the time is 10-20h.
4. The preparation method according to claim 1, characterized in that: (1) Drying treatment conditions: vacuum drying at 40-80°C for 24-48 hours.
5. The preparation method according to claim 1, characterized in that: (2) The flow rate of the CH4-Ar mixed flow is 20 to 80 mL / min.
6. The preparation method according to claim 1 or 5, characterized in that: (2) The volume ratio of CH4 to Ar in the CH4-Ar mixed flow is 1:
1.
7. The preparation method according to claim 1, characterized in that: (2) The heat treatment temperature is 200-600°C and the time is 30-90 minutes.
8. An alloy catalyst obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the alloy catalyst according to claim 8, characterized in that: Used to catalyze methane cracking reactions.
10. A method for low temperature catalytic cracking of methane, characterized in that: The alloy catalyst described in claim 8 is used as a cracking reaction catalyst, and the cracking reaction conditions are: under standard atmospheric pressure, the reaction temperature is 700-990°C, the CH4 gas flow rate is 6-60mL / min, and the protective gas Ar flow rate is 10-100mL / min.
Citation Information
Patent Citations
Methane cracking catalyst and preparation method thereof
CN111185179A
Nickel-gallium alloy catalyst as well as preparation method and application thereof
CN112705208A
Ni-M1-M2-M3 medium-entropy intermetallic compound catalyst as well as preparation method and application thereof
CN118059871A
Molten alloy catalyst for hydrogen production through methane cracking as well as preparation method and application of molten alloy catalyst
CN118437343A
A method for producing hydrocarbons by non-oxidative coupling of methane
EP3137441A1
